Reputasi Potret Kualitas Satisfaction Kereta Moda Raya Terpadu (MRT) Jakarta Berimplikasikan Kesinambungan Masyarakat - Fikri Aditya Mahendra; Muhammad Saddam Widodo; Muhammad Reza Alim Pratama; Siti Sahara (Institut Nalanda, 2023)
The slow and gradual congestion of roads with private vehicles has prompted the government to take quick action to address this issue. Preventive and even curative measures have been planned and carried out to minimize the accumulation of private vehicles. The government has a breakthrough in creating public transportation aimed at reducing the use of private vehicles. Certainly, something is needed to integrate the community as a means for them to reach their desired destinations. Not only integration, but also a breakthrough with adequate infrastructure and transportation modes that are of good quality, competent, flexible, and do not interfere with existing roads. Therefore, in Jakarta itself, there is a public transportation called the Mass Rapid Transit (MRT) which is used as an answer to the problem. According to the reputation obtained from data collected from the public, the advantage of this transportation is not only its ability to integrate the community, but also the infrastructure or construction that has a concept of being underground and several facilities that have good quality are some of its advantages.